Potencialidades do Jogo Africano Mancala IV para o campo da educação matemática, história e cultura africana - Pereira, Rinaldo Pevidor (2016)
PEREIRA, Rinaldo Pevidor. Potencialidades do Jogo Africano Mancala IV para o campo da educação matemática, história e cultura africana. 2016. 323f. – Tese (Doutorado) – Universidade Federal do Ceará, Programa de Pós-graduação em Educação Brasileira, Fortaleza (CE), 2016. === Submitted by Jackeline Costa (jackelinde@gmail.com) on 2016-12-07T13:29:02Z No. of bitstreams: 1 2016_tese_rppereira.pdf: 9031246 bytes, checksum: fee120332f7ccc184ca69aabaad61f68 (MD5) === Approved for entry into archive by Márcia Araújo (marcia_m_bezerra@yahoo.com.br) on 2016-12-08T12:28:06Z (GMT) No. of bitstreams: 1 2016_tese_rppereira.pdf: 9031246 bytes, checksum: fee120332f7ccc184ca69aabaad61f68 (MD5) === Made available in DSpace on 2016-12-08T12:28:06Z (GMT). No. of bitstreams: 1 2016_tese_rppereira.pdf: 9031246 bytes, checksum: fee120332f7ccc184ca69aabaad61f68 (MD5) Previous issue date: 2016 === The Law 10.639 / 03 deals with the compulsory inclusion of the teaching of history and afro-Brazilian culture, in schools teaching fundamental and medium, official and private. To this end, becomes required the training and capacity building of teachers in various areas of knowledge. In the field of mathematics, we concluded in the master's research, the possibility to articulate the teaching of mathematics to the Law 10.639/03, through in African Games, in particular, the Mancala game. Mancala is the term used of designate a family with more than two hundred variations of pits games, ranked by Mancala II, III and IV. At the master's, the research focused on Mancala II, as this is a variation of easy handling and the best known in the Western world. Already Mancala IV, is best known in East Africa and Asia. It is the most complex variation of these games, both in handling and in the mathematical operations involved in their practice. Moreover, this variation brings cultural practices from East Africa, little known to us Westerners. In this context, we realize the need to deepen the research that started in the master's with Mancala II for Mancala IV. In this sense, the thesis aims to investigate the potential of the African game Mancala IV to the field of mathematics education, the teaching of history and African culture. To this end, if intends build math concepts, as well as, build knowledge of African history and culture through from concrete situations of the game. This is a qualitative research with exploratory approach, kind ethnographic, which had as locus of research, three cities of Nampula Province in Mozambique. The research subjects were a group of thirty people, some of them members of the Provincial Association of Traditional Games of Nampula, others, intellectuals of the field of philosophy and sociology and, the vast majority, with little schooling. In Mozambique, the research was focused on two variations of Mancala IV, the M'pale and Mthadje. In the field of African history and culture, we concluded in the research what this game contributes to preserve the cultural identity of the African because, while they play, the elders teach to the younger, knowledges African ancestors. In practice the game, also if transmits philosophical and social values that contribute to living together collective. Among the studied african cultural referentials, we find the circularity, sharing, collectivity, ancestry, african worldview, religiosity, playfulness and orality. These references are also present in civilizing values african-Brazilians. In reazon of this, we concluded in this study that the Mancala IV game can also contribute for teaching history and afro-Brazilian culture. The Mancala IV is a strategy game that requires a lot of concentration and mental speed. It is mathematical game because in them are involved the mental calculation and simple and complex mathematical operations in his practice. The various possibilities of movements must be leveraged to build mathematical concepts systematized by the school. In this sense, we consider that this game can to be defined, depending on the orientation of the teacher, as a teaching material for the field of mathematics education, pedagogy, teaching history and afro-Brazilian culture and african. === A Lei 10.639/03 trata da obrigatoriedade de inclusão do ensino de história e cultura afro-brasileira, nos estabelecimentos de ensino fundamental e médio, oficial e particulares. Para tal, se faz necessário a formação e a capacitação de professores nas diversas áreas do saber. No campo da matemática, concluímos na pesquisa do mestrado, que é possível articular o ensino desta área do saber com a Lei 10.639/03, por intermédio de jogos africanos, em particular, o jogo Mancala. O termo Mancala é utilizado para designar uma família com mais de duzentas variações de jogos de covas, classificados por Mancala II, III e IV. No mestrado, a pesquisa concentrou-se no Mancala II, por ser esta, uma variação de fácil manuseio bem como a mais conhecida pelo mundo ocidental. Já o Mancala IV, é mais conhecido na África Oriental e na Ásia. É a variação mais complexa desses jogos, tanto em seu manuseio como nas operações matemáticas envolvidas em sua prática. Além disso, esta variação traz consigo práticas culturais provenientes da África Oriental, pouco conhecido por nós ocidentais. Foi neste contexto que percebemos a necessidade de aprofundarmos a pesquisa iniciada no mestrado com o Mancala II para o Mancala IV. Neste sentido, a tese se propõe a investigar as potencialidades do jogo africano Mancala IV para o campo da educação matemática, ensino de história e cultura africana. Para tanto, nos propomos a construir conceitos de matemática bem como conhecimentos sobre história e cultura africana a partir de situações concretas do jogo. Trata-se de uma pesquisa qualitativa com abordagem exploratória, tipo etnográfica, que teve como lócus da pesquisa, três cidades da província de Nampula em Moçambique. Os sujeitos da pesquisa foram um grupo de trinta pessoas, alguns deles, membros da Associação Provincial de Jogos Tradicionais de Nampula, outros, intelectuais do campo da filosofia e sociologia e, a grande maioria, com pouca instrução escolar. Em Moçambique, a investigação ficou centrada em duas variações do Mancala IV, o M’pale e o Mthadje. No campo da história e cultura africana, concluímos nesta pesquisa, que este jogo contribui para preservar a identidade cultural do africano, pois enquanto jogam, os anciões transmitem para os mais jovens, os saberes ancestrais africanos. Na prática do jogo, também se transmite valores filosóficos e sociais que contribuem para a convivência coletiva. Dentre os referenciais culturais africanos apurados, encontramos a circularidade, partilha, coletividade, ancestralidade, cosmovisão africana, religiosidade, ludicidade e oralidade. Estes referenciais também estão presentes nos valores civilizatórios afro-brasileiros. Sendo assim, concluímos nesta pesquisa que o jogo Mancala IV também pode contribuir para o ensino de história e cultura afro-brasileira. O Mancala IV é um jogo de estratégia que exige rapidez mental e muita concentração. É um jogo matemático por estar envolvido em sua prática o cálculo mental e operações matemáticas simples e complexas. As diversas possibilidades de movimentos podem ser potencializadas para a construção de conceitos matemáticos sistematizados pela a escola. Neste sentido, consideramos que este jogo pode contribuir, dependendo da orientação do professor, como um material didático para o campo da educação matemática, pedagogia, ensino de história e cultura africana e afro-brasileira.